A perfect storm: the deadly intersection of sickle cell disease and COVID-19 - Martí-Carvajal, Arturo José; De Sanctis, Juan Bautista (Frontiers in Hematology, 2025)
This review critically examines the latest research on the intersection of sickle cell disease (SCD) and COVID-19, highlighting meaningful immunopathological interactions. It reveals significant knowledge gaps, particularly in the analysis of inflammatory markers in clinical studies and the oversight of SCD in malaria-COVID-19 research conducted in African contexts. The investigation explores shared pathophysiological mechanisms, including the cytokine storm phenomenon, vascular complications, and autoimmune responses, which exemplify the perilous interplay between SCD’s chronic inflammatory state and the acute inflammatory response triggered by COVID-19. Furthermore, it provides a comprehensive analysis of hyperhaemolysis syndrome (HHS), related autoimmune conditions, and avascular necrosis (AVN) as critical complications affecting SCD patients during the COVID-19 pandemic. The aim is to establish a comprehensive framework for understanding this crucial intersection while proposing vital directions for future research and therapeutic interventions.